Surviving the sanctuary city : asylum-seeking work in Nepali New York - Shrestha, Tina (University of Washington Press, 2023)
"Surviving the Sanctuary City asks what everyday survival among migrants and asylum seekers can tell us about the cultural logic of suffering within the confines of US borders"--